THE PRINCIPLE OF THE RULE OF LAW IN THE SYSTEM OF LOCAL SELF-GOVERNMENT - Naila Ramiz gizi Gahramanova (International Journal of Innovative Technologies in Social Science, 2024)
The principle of the rule of law, or legal guarantee, plays a key role in the system of local government, providing a framework and restrictions for the actions of local authorities. This principle implies that all actions and decisions taken by local authorities must comply with the law, including legislation at higher levels of government, constitutional norms and local legal acts. The rule of law in the system of local self-government ensures legal stability, protection of the rights and freedoms of citizens, prevents arbitrariness and corruption, and also helps ensure justice and equality before the law for all members of society.